The Effectiveness of Early Detection of Heart Disease and Health Promotion on Attitude and Lifestyle Changes of Residents At Risk Of Heart Disease Post-Covid-19 Pandemic - Bara Miradwiyana; Suryati B Suryati B; Heni Nurhaeni; Kamsatun Kamsatun; Elsye Rahmawati (Green Publisher Indonesia, 2024)
During the Covid-19 pandemic, heart disease patients were at very high risk of experiencing severe complications if exposed to the virus. One important effort in preventing cardiovascular diseases is to identify the cardiovascular risk factors in each individual. There are several models for detecting risk, one of which is the Jakarta Cardiovascular Score. Health promotion is also an effort to manage modifiable risk factors for heart disease. Health promotion is expected to prevent risky behaviors that lead to an increase in heart disease incidence in the long term. This study aims to assess the effectiveness of early detection and health promotion in changing the attitudes and lifestyles of residents at risk of heart disease post-Covid-19 pandemic. The research method used in this study is a quasi-experimental design with one group of 30 respondents. The study was conducted in the working area of the Pasar Minggu District Health Center in Jakarta. The results showed that after the intervention, which included early detection and health promotion, there was a change in attitude by 0.8 points, from 88.13 (before intervention) to 88.95 (after intervention). The T-test results showed a p-value of 0.004, indicating a statistically significant difference between before and after the intervention. The respondents' lifestyle also changed by 5.5 points, from 66.03 (before intervention) to 71.62 (after intervention), with a p-value of 0.004, indicating a statistically significant difference between before and after the intervention.